Advertising and Conspicuous Consumption - Daniel Krähmer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
The paper formalizes the intuition that brands are consumed for image reasons and that advertising creates a brand's image. The key idea is that advertising informs the public of brand names and creates the possibility of conspicuous consumption by rendering brands a signalling device. In a price competition framework, we show that advertising increases consumers' willingness to pay and thus provide a foundation, based on optimization behavior, for persuasive approaches to advertising. Moreover, an incumbent might strategically overinvest in advertising to deter entry, there might be too much advertising, and competition might be socially undesirable.
urn:nbn:de:bvb:19-epub-13478-4
Keywords: 330